AUSTRALIA : A STUDY IN ABORIGINE CULTURAL PRESERVATION - Helfiana, Ayu (Jurnal Ilmiah Mahasiswa FIB, 2013)
Human power in dominating each other has occurred long ago as the development of the era that increasingly advances. Preservation is done to keep everything that is owned by a certain community which is a symbol of their identity. The writer conducted a study about cultural preservation by the Aborigines in 'Australia' movie which shows the cultural preservation toward White’s power occuring in Australia. There is a problem to be solved in the study, namely how the Aborigines struggle for preserving their culture.This study uses postcolonial approach because it is the most suitable with the ideology of the movie. The pressure of the Whites to the Aborigines is very interesting to be reviewed with the approach. There is interventions of the white people to regulate everything connected with the Aborigines inAustralia. In response, the Aborigines try very hard to preserve what they have in culture.The analysis reveals that all the actions taken by the Aborigines to preserve their culture are wearing traditional clothes, preserving life wisdoms and believing in superstitions. The Aborigines and the Whites do not have good relationship each other. The writer found that both of them try hard to maintain what they have. In this case the writer gives more emphasis on the Aborigines’ efforts to preserve their culture which have been passed down from their ancestors for many years. By this way, the culture is still preserved from generation to generation. King George in this movie acts as a teacher to teach all the habits of the Aborigines to his grandson, Nullah so that the opportunity for the Whites to change the culture of the Aborigines decreases.In conclusion, the Aborigines maintain their culture as their identity to be recognized in Australia because they are the indigenous inhabitants who have been living there. As Aborigines, they believe every place in the territory of Australia is a power for them because their culture is always related to the nature.